2018
DOI: 10.1002/anie.201808629
|View full text |Cite
|
Sign up to set email alerts
|

Processable Surface Modification of Nickel‐Heteroatom (N, S) Bridge Sites for Promoted Alkaline Hydrogen Evolution

Abstract: Nickel-heteroatoms bridge sites are important reaction descriptors for many catalytic and electrochemical processes.Herein we report the controllable surface modification of nickel-nitrogen (NiÀN) bridge sites on metallic Ni particles via asimplified vapor-assisted treatment approach. Xray absorption spectroscopy( XAS) and Operando Raman spectroscopyv erifies the interaction between Ni and surfaceanchored N, whichl eads to distorted Ni lattice structure with improved wettability.T he NiÀNb ridge sites with app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 24 publications
3
66
0
Order By: Relevance
“…As shown in Supplementary Fig. 4, the XRD patterns for Ni and Ni(Cu) are all crystalline with three main diffraction peaks at 2θ = 44.44°, 51.26°, and 76.35°, assigning to (111), (200), and (220) planes of face-centered cubic (fcc) Ni (JCPDS, No.70-0989) 17,26 . For Ni(Cu), the shoulder peaks appear at the base of Ni(111) and (200), indicating the partial formation of NiCu alloy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Supplementary Fig. 4, the XRD patterns for Ni and Ni(Cu) are all crystalline with three main diffraction peaks at 2θ = 44.44°, 51.26°, and 76.35°, assigning to (111), (200), and (220) planes of face-centered cubic (fcc) Ni (JCPDS, No.70-0989) 17,26 . For Ni(Cu), the shoulder peaks appear at the base of Ni(111) and (200), indicating the partial formation of NiCu alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Performance study revealed that Cr 2 O 3 coating was essential for maintaining the core NiO/Ni active sites from oxidation and aggregation. Recently, we demonstrated that Nmodified Ni catalysts with appropriate N coverage level plays a critical role towards electrochemical water splitting 17 . Experimental and density functional theory (DFT) calculations revealed that an appropriate N-coverage level can lead to favorable kinetics for H* adsorption and fast release of H 2 , and consequently enhanced activity and stability.…”
mentioning
confidence: 99%
“…To evaluatet he HER performance, we examined the activity of Ni-V 2 O 3 /NF by using at hree-electrode system in H 2 -saturated 1.0 m KOH. For comparison, Ni/NF,b lank NF,a nd commercial Pt/C (20 wt %P to nV ulcan carbonb lack) on glassy carbon www.chemsuschem.org À10 mA cm À2 at an extremelyl ow overpotential of only 25 mV (h 10 = 25 mV;F igure 4b), which was even lower than the value for the Pt/C catalyst( h 10 = 27 mV) and previously reported HER electrocatalysts, such as Ni, Zn-dual doped CoO NR (h 10 = 53 mV), [38] PtNi-O/C (h 10 = 39.8 mV), [39] Ni NPs/Ni-NC (h 10 = 147 mV), [40] Co/PCN (h 10 = 89 mV), [37] Ni-N 0.19 (h 10 = 42 mV) [41] and NiFeRu-LDH(h 10 = 29 mV) [42] (more comparisons are given in Table S1). In sharp contrast, Ni/NF (h 10 = 198 mV) and blank NF (h 10 = 295 mV) showedm uch largerH ER overpotentials.…”
mentioning
confidence: 60%
“…Ni‐V 2 O 3 /NF exhibited nearly zero onset HER overpotential (Figure a). Moreover, the Ni‐V 2 O 3 /NF sample reached a current density of −10 mA cm −2 at an extremely low overpotential of only 25 mV ( η 10 =25 mV; Figure b), which was even lower than the value for the Pt/C catalyst ( η 10 =27 mV) and previously reported HER electrocatalysts, such as Ni, Zn‐dual doped CoO NR ( η 10 =53 mV), PtNi‐O/C ( η 10 =39.8 mV), Ni NPs/Ni‐NC ( η 10 =147 mV), Co/PCN ( η 10 =89 mV), Ni‐N 0.19 ( η 10 =42 mV) and NiFeRu‐LDH( η 10 =29 mV) (more comparisons are given in Table S1). In sharp contrast, Ni/NF ( η 10 =198 mV) and blank NF ( η 10 =295 mV) showed much larger HER overpotentials.…”
Section: Figurementioning
confidence: 99%
“…[10] Thus, it is necessary to explore cost-effective and abundant non-noble metal-based catalysts for HER. [11] Recently, transition metal-based catalyst [12] and its nitrides, [13,14] phosphatides, [15][16][17][18] carbides [19,20] and sulfides [21,22] have been explored as efficient HER electrocatalysts. In particular, MoS 2 has been reported remarkable catalytic performance towards HER.…”
Section: Introductionmentioning
confidence: 99%